Performance improvement of EPDM and EPDM/Silicone rubber composites using modified fumed silica, titanium dioxide and graphene additives. (April 2020) - Azizi, Sohrab; Momen, Gelareh; Ouellet-Plamondon, Claudiane; David, Eric
Abstract: In this work, a polymeric composite was prepared from ethylene propylene diene monomer (EPDM) and silicone rubber (S) with additives of modified fumed silica (MFS), titanium dioxide (TiO2 ) and graphene. The dielectric and thermal performances of the EPDM-based composites were studied. An increase in the dielectric constant and AC dielectric breakdown strength was observed for the EPDM rubber composites containing MFS, TiO2, and graphene additives. In addition, the incorporation of the additives resulted7in a significant increase in the thermal stability ( 30–50 °C) and thermal conductivity ( 7–35%) of the composites. The combination of these various improvements gives suitable performance advantage to the polymeric composite for use in insulating applications. Highlights: EPDM and silicone (S) rubbers composites were compounded via mechanical mixing. The thermal stability of the EPDM and EPDM/silicone rubber composites was increased. The dielectric breakdown strength of the EPDM composites was increased by additives loading. TGA-FTIR analysis revealed the thermal degradation of the rubber composites. Utilizing TiO2, MFS and graphene appeared to mitigate the destructiove incidents in HV insulating materials.